Respuesta :

Answer:

The value of  [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex]  at t = √2 is  [tex]\frac{1}{2 \times \sqrt{2}}[/tex] .

Step-by-step explanation:

Given as :

x = t³ - 3 t

y = 3 t²

We have to calculate [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] at t = √2

Now,

[tex]\frac{\mathrm{d} x}{\mathrm{d} t}[/tex] = [tex]\frac{\mathrm{d} (t³ - 3 t)}{\mathrm{d} t}[/tex]  

Or, [tex]\frac{\mathrm{d} x}{\mathrm{d} t}[/tex] = [tex]\frac{\mathrm{d}  t³}{\mathrm{d} t}[/tex] - 3 [tex]\frac{\mathrm{d}  t}{\mathrm{d} t}[/tex]

Or, [tex]\frac{\mathrm{d} x}{\mathrm{d} t}[/tex] = 3 t² - 3        ......A

Again

[tex]\frac{\mathrm{d} y}{\mathrm{d} t}[/tex] = [tex]\frac{\mathrm{d} (3 t²)}{\mathrm{d} t}[/tex]  

Or, [tex]\frac{\mathrm{d} y}{\mathrm{d} t}[/tex] = 3 × 2 t

Or, [tex]\frac{\mathrm{d} y}{\mathrm{d} t}[/tex] = 6 t           ......B

So,

[tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] = [tex]\frac{\frac{\partial y}{\partial t}}{\frac{\partial x}{\partial t}}[/tex]

Or, [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] = [tex]\dfrac{3 t^{2} - 3 }{6 t}[/tex]

Or,  [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] = [tex]\frac{3(t^{2}-1)}{6 t}[/tex]

Or,  [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] = [tex]\frac{(t^{2}-1)}{2 t}[/tex]

Or,  [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex]  at t = √2

i.e  [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] = [tex]\frac{(\sqrt{2}^{2}-1)}{2 \times \sqrt{2}}[/tex]

Or, [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] = [tex]\frac{(2-1)}{2 \times \sqrt{2}}[/tex]

Or, [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex] = [tex]\frac{1}{2 \times \sqrt{2}}[/tex]

Hence, The value of  [tex]\frac{\mathrm{d} y}{\mathrm{d} x}[/tex]  at t = √2 is  [tex]\frac{1}{2 \times \sqrt{2}}[/tex] . Answer